Financial distress and perceived stress among university students in Health Sciences - Khoo, Kenny K.L.; Nor M.F. Farah, (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2021)
College or university life is a period of significant life transition typically marked by an increase in financial responsibility. Lack of economic support and financial distress are rising concerns at many higher learning institutions today and can be a potential stress factor for many students. The aim of this study was to determine the financial status, levels of financial distress, perceived stress and life satisfaction among university students studying health-related fields. This was a cross-sectional study conducted among 100 undergraduate students from the Faculty of Pharmacy (n=35), Faculty of Health Sciences (n=36) and Faculty of Dentistry (n=29). The In-Charge Financial Distress/Financial Wellbeing scale, Perceived Stress Scale and Satisfaction with Life Scale questionnaires were used to determine perceived financial distress and stress, as well as life satisfaction respectively. In addition, socioeconomic and demographic data were also collected. Data analysis included comparing levels of financial distress, perceived stress, as well as life satisfaction among sociodemographic factors, as well as associations between financial distress with perceived stress and life satisfaction. The study respondents were consisted of 2nd (n=35), 3rd (n=32) and 4th (n=33) year students. A majority of the respondents were Malays (44%), followed by Chinese (38%), and Indians (12%). About 46% of the respondents were fully dependent on scholarships or PTPTN loans, 24% were funded by parents while the rest either received part study loans or funded by both scholarships/loans and parents. The average total monthly expenditure was reported to be RM 717 ± 296. The highest monthly expenditures were recorded among Chinese students (RM 816 ± 286) compared to the rest. The mean scores for financial distress, perceived stress and life satisfaction were 5.8 ± 1.9 (CI: 5.4 – 6.2), 21.2 ± 5.6 (CI: 20.1 – 22.3) and 22.2 ± 5.4 (CI: 21.1 – 23.2) respectively. Overall, the students in the study showed moderate levels of financial distress and perceived stress. Correlation analysis indicated that greater financial distress was associated with greater perceived stress. Factors impacting university students’ financial distress should be investigated along with ways to overcome them in future studies.